An experimental demonstration that predation influences antelope sex ratios and resource-associated mortality - O'Kane, C; Macdonald, D (Elsevier, 2015)
Smaller, enclosed reserves lacking large mammalian predators are an increasingly popular commercial model in southern Africa and elsewhere. The presence or absence of predation is likely to have major effects on the population dynamics of sexually dimorphic ungulates, with contradictory implications for multiple-use reserves, and to provide fundamental insights into predator–prey relationships.